Evidence for light-by-light scattering and searches for axion-like particles in ultraperipheral PbPb collisions at $\sqrt{s_NN} =$ 5.02 TeV - CMS Collaboration (2018)
Evidence for the light-by-light scattering process, $γγ$ $→$ $γγ$, in ultraperipheral PbPb collisions at a centre-of-mass energy per nucleon pair of 5.02 TeV is reported. The analysis is conducted using a data sample corresponding to an integrated luminosity of 390 $μ$b$^{-1}$ recorded by the CMS experiment at the LHC. Light-by-light scattering processes are selected in events with two photons exclusively produced, each with transverse energy E$_T^{γ}$ $>$ 2 GeV, pseudorapidity $|η^{γ}|$ $\lt$ 2.4, diphoton invariant mass $m^{γγ}$ $\gt$ 5 GeV, diphoton transverse momentum $p_T^{γγ}$ $\lt$ 1 GeV, and diphoton acoplanarity below 0.01. After all selection criteria are applied, 14 events are observed, compared to expectations of 9.0 $±$ 0.9 (theo) events for the signal and 4.0 $±$ 1.2 (stat) for the background processes. The excess observed in data relative to the background-only expectation corresponds to a significance of 3.7 standard deviations, and has properties consistent with those expected for the light-by-light scattering signal. The measured fiducial light-by-light scattering cross section, $σ_fid (γγ$ $→$ $γγ) =$ 120 $±$ 46 (stat) $±$ 28 (syst) $±$ 12 (theo) nb, is consistent with the standard model prediction. The $m^{γγ}$ distribution is used to set new exclusion limits on the production of pseudoscalar axion-like particles, via the $γγ$ $→$ a $→$ $γγ$ process, in the mass range $m_{a} =$ 5-90 GeV.